Rapid Manufacturing Method of Cardiovascular Models for Experimental Flow Analysis - Jarrett Fowler; Andrew B. Robbins; Cathryn Gunawan; Andrew Jastram; Michael Moreno (MethodsX)
Physical anatomical models constructed from medical images are valuable research tools for evaluating patient-specific clinical circumstances. For example, 3D models replicating a patient's internal anatomy in the cardiovascular system can be used to validate Computational Fluid Dynamics (CFD) models, which can then be used to identify potential hemodynamic consequences of surgical decisions by providing insight into how blood and vascular tissue mechanics may contribute to disease progression and post-operative complications. Patient-specific models have been described in the literature; however, rapid prototyping models that achieve anatomical accuracy, optical transparency, and thin-walled compliance in a cost and time-effective approach have proven challenging. This limits their utility for modeling flows in vessels, e.g., the aorta, where compliance is particularly important. The work described herein is focused on a unique design and fabrication process implemented to produce physical patient-specific models that replicate the original anatomy dimensions and compliance with optical properties consistent with clinical imaging techniques. The patient-specific models are produced for under $150 of easily accessible consumable raw materials within 30 h using a relatively basic approach. • This method can be tuned for anatomies with different shapes and compliance. • This method can produce models to investigate medical device performance in vitro.